New experimental model of exposure to environmental tobacco smoke - Brito,Marcus Vinicius Henriques (2013)
PURPOSE: To describe a new model to passive smoking for rodents. METHODS: Twenty rats were distributed into two study groups (N=10): control group (CG), that was not exposed to tobacco smoke and used as normal standard for biochemical and histological analysis; Experimental Group (EG), that Animals were exposed to the passive smoking; Euthanasia was performed after 14 days of exposure. The serum level of nicotine and histological analysis were performed. RESULTS: There was a statistical difference on the nicotine serum levels between Experimental and Control group, with level of 286 ±23 nanograma/mL in the EG and undetectable on CG (p<0.01). The histological study suggested the model efficacy producing alveolar destruction and emphysema in the EG compared with the insignificant lesions in the CG's lung. CONCLUSION: The model of exposure to environmental tobacco smoke for rodents induced easily the changes related to secondhand smoke.